Performance evaluation of old industrial city transformation based on the GRA-VIKOR-coupling coordination degree method - Chen, Yunyun; Guo, Jeen; Qi, Lingling; Zhu, Yuyi (Frontiers in Built Environment, 2025)
IntroductionSince the beginning of the twenty-first century, with the depletion of resources, the decline of industries and the impact of emerging technologies, old industrial bases have faced problems such as an aging economic structure, weak growth, deterioration of the ecological environment, and the backwardness of public facilities, which have severely constrained the sustainable development of cities. Although the government has continued to invest a large amount of resources to promote the transformation of old industrial zones, there are significant differences in the effectiveness of the transformation between regions from a national perspective, with some areas achieving significant results and others still facing economic and social difficulties.MethodsThis study aims to construct an evaluation index system for the transformation performance of old industrial cities and use a combination empowerment model based on the game-theoretic combined weighted approach and the GRA-VIKOR-coupling coordination degree comprehensive evaluation model. Specific regions, including the Dadukou District in Chongqing, the Huaxi District in Guiyang, and the Baqiao District in Xi’an, were selected as sample cases to diagnose the transformation performance and evolutionary characteristics of coupled coordinated development in old industrial cities from 2012 to 2023, and an in-depth analysis of the issues encountered during the transformation process was conducted.ResultsThe results of the study found that: (1) Overall, the comprehensive transformation performance of the three old industrial cities exhibited a fluctuating upward trend during the study period, verifying the positive impact of China’s policy support and industrial structure optimization for old industrial cities. (2) According to the results of the coupling coordination degree, the overall trend of the coupling coordination level of the three-dimensional system shows an upward trend, and the degree of coordination increases from the “dysfunctional recession zone” to the “coordinated development zone” level.ConclusionBased on the above conclusions, this study puts forward targeted policy recommendations that aim to provide valuable references for promoting the high-quality development of old industrial cities.